Willingness to Pay vs. Willingness to Accept: Legal and Economic Implications - Elizabeth Hoffman; Matthew L. Spitzer (Washington University Law Quarterly, 1993)
This Article presents, organizes, and critiques the modem evidence on the basic independence assumption, drawing together the learning of economists and lawyers.
Keywords: Economics